Educational Achievement and Ethnicity in Compulsory Schooling - Christian Dustmann; Stephen Machin; Uta Schoenberg (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
This paper analyzes the evolution of the attainment gap between white British born and ethnic minority pupils throughout compulsory schooling, from the age of 5 to 16. At the start of school, pupils from most ethnic groups substantially lag behind White British pupils, but these gaps decline for all groups throughout primary and secondary school. Language is the single most important factor why most ethnic minority pupils improve relative to White British pupils. Although poverty explains part of the differences in levels, it cannot explain why ethnic minority pupils gain relative to or even overtake White British pupils. All ethnic minority groups initially attend worse performing schools than White British pupils. However, more than 20 percent of the subsequent relative improvement can be attributed to ethnic minority pupils moving up to better schools relative to White British pupils. Finally, our results suggest the possibility that the relative improvement of ethnic minority pupils may be related to teacher incentives to concentrate attention on particular pupils, caused by the publication of school league tables at the end of secondary school.
Keywords: 330